Epithelial–mesenchymal transition in pulmonary fibrosis: molecular mechanisms and emerging therapeutic strategies - Li, Weiyi; Xie, Yinghai; Chen, Zhenzhen; Cao, Dongli; Wang, Yu (Frontiers in Medicine, 2025)
Pulmonary fibrosis is a progressive lung-scarring disease for which curative options remain limited. This review examines how epithelial–mesenchymal transition (EMT) contributes to fibrotic remodeling in subsets of pulmonary fibrosis (PF), delineates where the evidence is strongest, and highlights emerging therapeutic directions. PF encompasses idiopathic PF (IPF) and diverse non-IPF interstitial lung diseases driven by autoimmunity, exposures, or genetics, in which EMT involvement is variable. Recent laboratory and clinical work has been analyzed and the evidence grouped into four areas: well-known growth-factor signals; immune and inflammatory crosstalk; newer drivers such as iron-linked cell death, metabolic change and tissue stretch; and emerging medicines that temper these pathways, including licensed antifibrotics, experimental small molecules, natural compounds and RNA-based agents. Collectively, EMT emerges as a potentially reversible hub linking epithelial stress to scar formation, suggesting stage-specific combination strategies supported by single-cell profiling, lung organoids, and targeted delivery.